HOTEL AND RESTAURANT EDUCATION THROUGH THE PRISM OF GLOBALISATION PROCESSES - Будник, Ніна; Мороз, Світлана; Калашник, Олена; Левченко, Юлія (SWorldJournal, 2025)
The article explores the evolving role of hospitality education amidst globalization, emphasizing its significance in shaping professionals who represent national economies and cultures on a global stage. It addresses the dual challenge of aligning with i